Evolution towards asymptotic efficiency, preliminary version - Stefano Demichelis (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
We show that in long repeated games, or in infinitely repeated games with discount rate close to one, payoffs corresponding to evolutionary stable sets are asymptotically efficient, as intuition suggests. Actions played at the beginning of the game are used as messages that allow players to coordinate on Pareto optimal outcomes in the following stages. The result builds a bridge between the theory of repeated games and that of communication games.
Keywords: 330